1992
DOI: 10.2105/ajph.82.11.1483
|View full text |Cite
|
Sign up to set email alerts
|

Community AIDS/HIV risk reduction: the effects of endorsements by popular people in three cities.

Abstract: OBJECTIVES. It is critical to extend community-level acquired immunodeficiency syndrome (AIDS) prevention efforts beyond education alone and to develop models that better encourage behavioral changes. Gay men in small cities are vulnerable to human immunodeficiency virus (HIV) infection due to continued high rates of risk behavior. This research introduced an intervention that trained popular people to serve as behavioral change endorsers to peers sequentially across three different cities. METHODS. Population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
200
0
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(211 citation statements)
references
References 6 publications
8
200
0
3
Order By: Relevance
“…Also, perceived likelihood of infection was not associated with lower risk behaviors. The final finding was that, even though peer educators had been useful among non-runaways in significantly reducing the frequency of unprotected anal intercourse among men who have sex with men (Kelly et al 1992), this intervention was not effective in changing risk behaviors, especially sex behaviors among runaways. Analyses indicated that only runaways in the control condition reduced their sex risks over time.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Also, perceived likelihood of infection was not associated with lower risk behaviors. The final finding was that, even though peer educators had been useful among non-runaways in significantly reducing the frequency of unprotected anal intercourse among men who have sex with men (Kelly et al 1992), this intervention was not effective in changing risk behaviors, especially sex behaviors among runaways. Analyses indicated that only runaways in the control condition reduced their sex risks over time.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Diffusion theory posits that behavioral change is achieved when information and ideas, such as new risk-reducing methods in the case of HIV prevention, is disseminated by opinion leaders through their personal and social networks (Sivaram et al, 2004). Kelly and colleagues have shown that systematically identified, recruited, and trained POLs make a positive impact on sexual behavior change in populations of men attending gay bars in the United States (Kelly et al, 1991;Kelly et al, 1992;Kelly et al, 1997). In the POL model, ethnographic techniques are employed to systematically identify popular and socially influential members of the target population.…”
mentioning
confidence: 99%
“…It also employed two important aspects of peer education: using peers as opinions leaders and models in relation to moderate alcohol use (Kelly et al, 1992); and encouraging young people to think critically about their own behavior in a "binge drinking" youth culture (Campbell & MacPhaill, 2002).…”
Section: Discussionmentioning
confidence: 99%